2012
DOI: 10.1186/1475-9276-11-12
|View full text |Cite
|
Sign up to set email alerts
|

The social gradient in doctor-patient communication

Abstract: ObjectiveIn recent years, the importance of social differences in the physician-patient relationship has frequently been the subject of research. A 2002 review synthesised the evidence on this topic. Considering the increasing importance of social inequalities in health care, an actualization of this review seemed appropriate.MethodsA systematic search of literature published between 1965 and 2011 on the social gradient in doctor-patient communication. In this review social class was determined by patient's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
194
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(213 citation statements)
references
References 55 publications
(91 reference statements)
12
194
4
3
Order By: Relevance
“…[28][29][30] Our finding that consultations in deprived areas were less patient-centered agrees with a review of the literature that found that physicians are generally much more directive with patients of low educational status. 31 Perceived GP empathy (as gauged by the CARE measure) was also lower in the deprived group than the affluent, and empathy was a significant independent predictor of better outcomes at 1 month in both deprived and affluent groups. This adds to the growing evidence base on the importance of physician empathy in achieving good patient outcomes.…”
Section: Relationship To Published Literaturementioning
confidence: 88%
“…[28][29][30] Our finding that consultations in deprived areas were less patient-centered agrees with a review of the literature that found that physicians are generally much more directive with patients of low educational status. 31 Perceived GP empathy (as gauged by the CARE measure) was also lower in the deprived group than the affluent, and empathy was a significant independent predictor of better outcomes at 1 month in both deprived and affluent groups. This adds to the growing evidence base on the importance of physician empathy in achieving good patient outcomes.…”
Section: Relationship To Published Literaturementioning
confidence: 88%
“…For example, it has been reported that more-deprived individuals receive a lower quality of care (Hall and Dornan 1990), spend less time with a doctor (Videau et al 2010) and receive less information (Willems et al 2005). Sociological explanations for these divergences are scarce (Willems et al 2005), but important insights could be derived from the observation that patients in a higher socioeconomic position secure more information from doctors, through effective expressiveness and assertiveness (Verlinde et al 2012). This active stance precisely constitutes the underlying idea for Shim (2010) developing how cultural health capital may shape the content and tone of patientprovider interactions.…”
Section: Resultsmentioning
confidence: 99%
“…We found no significant relationship between communication orientation skill and patient enablement. HCPs might have different perspectives of their communication skill, while patients perceived them differently (Verlinde et al 2012: Khalid & Farid, 2010.…”
Section: Discussionmentioning
confidence: 99%